Assessment of Possibilities for Operation of Ni-Catalyst Partial Oxidation Reformers in SOFC Systems after Soot Formation. (2nd June 2015) - Baskakov, Albert Pavlovich; Plotnikov, Nikita; Wang, W.; Peng, J.; Volkova, Yulia; Dong, Z; Lu, X; Luo, Q
Abstract : Solid oxide fuel cells (SOFCs) allow us to directly convert the chemical energy of fuel into electricity. With their emissions consisting mainly of Н2 О and СО2, SOFC-based power generation systems are highly efficient (with efficiency up to 70%) and friendly to the environment, which makes them increasingly attractive for the use in stationary power generation systems. The mixture of CO and H2 (synthesis gas) supplied to the SOFC anode can be produced from the natural gas using the dry or steam reforming or the partial oxidation methods. The partial oxidation of methane, which is typically done with Ni catalysts, seems the best option for start-up systems of power plants with the anode gas recirculation or other applications where no water supply can be arranged. In this case, carbon deposition on the parts of reformer can be a problem, particularly, where the air-gas mixture supply system works abnormally.